Predictors of transitions from single to multiple job holding: Results of a longitudinal study among employees aged 45‐64 in the Netherlands. Issue 8 (10th July 2017) - Bouwhuis, Stef; Geuskens, Goedele A.; Boot, Cécile R. L.; Bongers, Paulien M.; van der Beek, Allard J.
Abstract : Objectives: To construct prediction models for transitions to combination multiple job holding (MJH) (multiple jobs as an employee) and hybrid MJH (being an employee and self‐employed), among employees aged 45‐64. Methods: A total of 5187 employees in the Netherlands completed online questionnaires annually between 2010 and 2013. We applied logistic regression analyses with a backward elimination strategy to construct prediction models. Results: Transitions to combination MJH and hybrid MJH were best predicted by a combination of factors including: demographics, health and mastery, work characteristics, work history, skills and knowledge, social factors, and financial factors. Not having a permanent contract and a poor household financial situation predicted both transitions. Some predictors only predicted combination MJH, e.g., working part‐time, or hybrid MJH, e.g., work‐home interference. Conclusions: A wide variety of factors predict combination MJH and/or hybrid MJH. The prediction model approach allowed for the identification of predictors that have not been previously studied.